2019
DOI: 10.1155/2019/3415630
|View full text |Cite
|
Sign up to set email alerts
|

The Basics of Sentinel Lymph Node Biopsy: Anatomical and Pathophysiological Considerations and Clinical Aspects

Abstract: Sentinel lymph node (SLN) is the first node to receive the drainage directly from a tumor. Detection and pathological examination of the SLN is an important oncological procedure that minimizes morbidity related to extensive nodal dissection. SLN biopsy was first reported in 1960 but took approximately 40 years to come into general practice following reports of good outcomes in patients with melanoma. After many years of observation and research on its use in various malignancies SLN biopsy has become the stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…Sentinel lymph node (SLN) mapping techniques have been developed in human oncology to identify the first LN(s) receiving the lymph from tumours that predominantly spread through the lymphatic system. 14 Regional lymphoscintigraphy combined with intra-operative lymphoscintigraphy and blue dye, the gold standard SLN mapping technique in human oncology, has been successfully incorporated into canine MCT staging in previous studies. 15,16 Lymphoscintigraphy is however, only available in very few veterinary centres.…”
mentioning
confidence: 99%
“…Sentinel lymph node (SLN) mapping techniques have been developed in human oncology to identify the first LN(s) receiving the lymph from tumours that predominantly spread through the lymphatic system. 14 Regional lymphoscintigraphy combined with intra-operative lymphoscintigraphy and blue dye, the gold standard SLN mapping technique in human oncology, has been successfully incorporated into canine MCT staging in previous studies. 15,16 Lymphoscintigraphy is however, only available in very few veterinary centres.…”
mentioning
confidence: 99%
“…I n the evaluation of breast cancer, sentinel lymph node (SLN) status provides vital prognostic information used to establish next steps in treatment. 1,2 Detecting positive SLNs allows the surgeon to consider performance of axillary lymph node dissection (ALND). Sentinel lymph node frozen section (FS) evaluation has been used to avoid delaying ALND.…”
mentioning
confidence: 99%
“…On the contrary, our study revealed that a signi cant number of surgeons, mainly working in hot COVID-19 hospitals did not perform SLN in their practice during the pandemic. SLN biopsy is the recommended approach, particularly for endometrial and cervical cancer patients decreasing total operation time and morbidity related to systemic lymphadenectomy (21,22). However, because of the issues such as long learning curve, need for experience, and logistic problems (availability of tracer), the use of and preference for the SLN concept might decrease during the pandemic (23).As seen from different studies, the preferences of the route of the surgery (laparotomy or laparoscopy), the use of the SLN concept depended on geographic region, the status of the hospital, the experience of the surgeon (17,19,24).…”
Section: Discussionmentioning
confidence: 99%